Antimicrobial Photodynamic Therapy for the Treatment of Antibiotic-Resistant Surgical Infections - Shuxrat Isakov; Khasan Jafarov; Erkin Zakhidov; Mukhibjon Imomov; Berdimuratov Temurbek Aymurzaevich; Sadat Bayzhigitova (Academia Open, 2026)
General Background: The global rise of antibiotic resistance has become a critical challenge in modern medicine, contributing to increased mortality, prolonged hospitalization, and economic burden. Specific Background: Antibiotic-resistant pathogens such as methicillin-resistant Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter spp., and Pseudomonas aeruginosa are frequently associated with nosocomial infections in postoperative patients. Knowledge Gap: The declining efficacy of conventional antibacterial drugs necessitates the exploration of alternative antimicrobial strategies. Aims: This study aimed to improve strategies for controlling antibiotic-resistant microorganisms through the application of antimicrobial photodynamic therapy using methylene blue. Results: In vitro findings demonstrated that methylene blue and laser irradiation (632 nm) applied independently showed no antimicrobial activity, whereas their combined application produced a pronounced bactericidal effect. The highest inhibition zones were observed for Acinetobacter spp. (up to 40 ± 1.6 mm), followed by Pseudomonas aeruginosa, Klebsiella pneumoniae, and MRSA. Novelty: The study highlights the strong antimicrobial potential of methylene blue–mediated photodynamic therapy against a broad spectrum of resistant microorganisms. Implications: This approach represents a promising alternative method for the treatment and prevention of infectious complications in surgical practice, particularly in the context of increasing antimicrobial resistance. Highlights:• Combined Light and Photosensitizer Application Produces Strong Bactericidal Activity• Highest Microbial Inhibition Observed in Acinetobacter Species Cultures• Broad-Spectrum Action Against Gram-Positive and Gram-Negative Resistant Pathogens Keywords: Photodynamic Therapy, Antibiotic Resistance, Methylene Blue, Nosocomial Infections, Surgical Infections.